2020
DOI: 10.1001/jamasurg.2020.3672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Embolization on Patients With Blunt Trauma at High Risk of Splenectomy

Abstract: IMPORTANCE Splenic arterial embolization (SAE) improves the rate of spleen rescue, yet the advantage of prophylactic SAE (pSAE) compared with surveillance and then embolization only if necessary (SURV) for patients at high risk of spleen rupture remains controversial. OBJECTIVE To determine whether the 1-month spleen salvage rate is better after pSAE or SURV. DESIGN, SETTING, AND PARTICIPANTSIn this randomized clinical trial conducted between February 6, 2014, and September 1, 2017, at 16 institutions in Franc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…Further, additional studies have pointed out the advantages of endovascular management in having lower risk than traditional surgical approaches while allowing for precise localization of the PA as well as assessment of the collateral vasculature (Hemp and Sabri 2015;Clark et al 2017;Salam et al 1992). Recent randomized controlled data has additionally shown that prophylactic splenic artery embolization after high risk splenic trauma results in fewer splenic PAs, secondary embolizations, and shorter hospitalizations, without increasing complication rates or compromising future splenic viability compared to surveillance (Arvieux et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further, additional studies have pointed out the advantages of endovascular management in having lower risk than traditional surgical approaches while allowing for precise localization of the PA as well as assessment of the collateral vasculature (Hemp and Sabri 2015;Clark et al 2017;Salam et al 1992). Recent randomized controlled data has additionally shown that prophylactic splenic artery embolization after high risk splenic trauma results in fewer splenic PAs, secondary embolizations, and shorter hospitalizations, without increasing complication rates or compromising future splenic viability compared to surveillance (Arvieux et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Arvieux et al [ 86 ] randomized 140 patients with splenic trauma at high risk of rupture (AAST Grade III with large pelvic hemoperitoneum and/or serious damage with a New Injury Severity Score of 15 or more, Grade IV splenic trauma, or Grade V splenic trauma with persisting vascularization of the spleen) to prophylactic SAE (pSAE) or surveillance and then embolization only if necessary (SURV); 133 patients were retained in the study. For the primary endpoint (1-month spleen salvage), data from 117 patients (57 who underwent pSAE and 60 who underwent SURV) were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…A recent randomized trial from France, however, comparing prophylactic SAE vs surveillance and embolization only if necessary found no difference in splenic salvage rates between groups, with both reporting rates greater than 93%. 32 Splenic angioembolization was avoided in 68% of patients in the surveillance group. Of note, the authors did not comment on the indications for patients who ultimately underwent SAE in the observation group.…”
Section: Historical Evolution Of Splenic Artery Angioembolizationmentioning
confidence: 99%